Komodifikasi Nilai Kesakralan (Transformasi Fungsi Ruang Dalam Perspektif Heterotopia di Pura Dalem Ped) - Nyoman Ayu Sukma Pramestisari; Ni Luh Nyoman Kebayatini; Kadek Aryana Dwi Putra (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, Denpasar-Bali, Indonesia, 2023)
The development agenda to improve people's welfare is still the dominant discourse. In the case of the Province of Bali, since the early 1980s the development of the tourism industry with the cultural tourism axis has been the main spirit of development. One of the logical consequences of this development agenda is the commodification of sacred spaces. The commodification of sacred spaces can be seen from the social reality at Dalem Ped Temple. Where now Dalem Ped Temple is not limited to being a sacred space for a place of worship for the Hindu community, but has developed into a tourism space to a capital accumulation space for local managers and traders. Various social spaces created as a result of the commodification of sacred values in Dalem Ped Temple are referred to as heterotopia spaces. In other words, an alternative space is created in a multifunctional space that is in one place.